Delegacias de atendimento à mulher : caminhos que se abrem e que se fecham - Gava, Rafael Ambrósio (2016)
Despite the numerous studies that have been done trying to understand why the promises made with the approval of Maria da Penha Law have not yet fully and satisfactory come to be, few set out to understand the dynamics in the Police Stations for Assistance to Women (DEAM's ) of the Espírito Santo (ES) – Brazilian state that holds the highest female homicides rate. Thus, by the end of 2013, we started an ethnographic study in three Grande Vitória’s DEAM's (region in which lives almost half of the Espírito Santo’s population) in order to analyze the dynamics in these organs and find out if it can help explain why ES have such high rates of violence against women. Throughout the study, the arrival women these Police Stations and the "screening procedure" played in these organs called our attention. Despite the peculiarities inherent to each of the stations surveyed, we perceived the adoption of similar practices and rituals in all three DEAMs. These rituals of social interaction (as well as the social representations within them) heavily influence the construction of the legal discourse produced in those areas and thus the way the Maria da Penha Law is applied (or not) in each case. Based on social rules reinforced by these rituals, the agents occupying these spaces (police, witnesses, victims and perpetrators) construct criteria that guide how the rules should be applied in each case. This construction process is constantly marked by (pre)judgments, symbolic violence and "male dominance" that are shared and reinforced by the social agents. As a result, it is common to refuse claims or act in a way that discourage criminal percussion, which tends to reinforce the feeling ineffectiveness of Maria da Penha Law. Moreover, it is questionable whether the Maria da Penha Law adopts means able to tackle the real causes of gender violence. These empirical findings may be among the reasons why gender violence rates in the Espírito Santo are so high.